2018
DOI: 10.1111/eci.12899
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetic changes and their implications in autoimmune hepatitis

Abstract: Background: The genetic risk of autoimmune hepatitis is insufficient to explain the observed risk, and epigenetic changes may explain disparities in disease occurrence in different populations within and between countries. The goal of this review was to examine how epigenetic changes induced by the environment or inherited as a phenotypic trait may affect autoimmune hepatitis and be amenable to therapeutic intervention. Materials and methods: Pertinent abstracts were identified in PubMed by multiple search ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 253 publications
(543 reference statements)
1
36
0
1
Order By: Relevance
“…The pathogenic basis for the iron dysregulation in chronic liver diseases other than hereditary haemochromatosis is unclear, but it may relate to genetic ( HFE and non‐ HFE genes), epigenetic (toxins, nutrition), and disease‐related (cytokine responses, tissue hypoxia, hepatocyte damage) factors that disrupt iron homeostasis. The serum hepcidin response to the liver injury may be the pivotal factor in understanding the basis for the iron disturbance and directing management.…”
Section: Resultsmentioning
confidence: 99%
“…The pathogenic basis for the iron dysregulation in chronic liver diseases other than hereditary haemochromatosis is unclear, but it may relate to genetic ( HFE and non‐ HFE genes), epigenetic (toxins, nutrition), and disease‐related (cytokine responses, tissue hypoxia, hepatocyte damage) factors that disrupt iron homeostasis. The serum hepcidin response to the liver injury may be the pivotal factor in understanding the basis for the iron disturbance and directing management.…”
Section: Resultsmentioning
confidence: 99%
“…Kempinska-Podhorodecka et al found that in PBC livers, either cirrhotic or not, there is a significant impairment in VDR expression, resulting in enhancement of non-coding miR155 and consequent SOCS1 reduction, which probably interferes with the negative feedback on pro-inflammatory cytokines response [275]. Actually, VDR is also an important receptor for ursodeoxycholic acid (UDCA) inducing cathelicidin expression in biliary epithelial cells [243]; it also mediates many epigenetic effects, which contribute to the reduction of pro-inflammatory cytokines synthesis [276].…”
Section: Vitamin D and Autoimmune Liver Diseasesmentioning
confidence: 99%
“…Genetic mutations have been identified as causing or enhancing susceptibility for each of these diseases; however, such mutations are observed in the minority of patients, suggesting that alternative factors regulate disease incidence. In addition, these diseases have highly variable presentation between patients, and this variability is not fully explained by inherited genetic factors [110]. Thus, aspects of these diseases are likely to be regulated by epigenetic mechanisms.…”
Section: Epigenetic Dynamics In Non-neoplatic Diseasesmentioning
confidence: 99%